Alvespimycin Inhibits Heat Shock Protein 90 and Overcomes Imatinib Resistance in Chronic Myeloid Leukemia Cell Lines - Alves, Raquel (2023)
Heat shock protein 90 (HSP90) facilitates folding and stability and prevents the degradation of multiple client proteins. One of these HSP90 clients is BCR-ABL, the oncoprotein characteristic of chronic myeloid leukemia (CML) and the target of tyrosine kinase inhibitors, such as imatinib. Alvespimycin is an HSP90 inhibitor with better pharmacokinetic properties and fewer side effects than other similar drugs, but its role in overcoming imatinib resistance is not yet clarified. This work studied the therapeutic potential of alvespimycin in imatinib-sensitive (K562) and imatinib-resistant (K562-RC and K562-RD) CML cell lines. Metabolic activity was determined by the resazurin assay. Cell death, caspase activity, mitochondrial membrane potential, and cell cycle were evaluated by means of flow cytometry. Cell death was also analyzed by optical microscopy. HSPs expression levels were assessed by western blotting. Alvespimycin reduced metabolic activity in a time-, dose-, and cell line-dependent manner. Resistant cells were more sensitive to alvespimycin with an IC50 of 31 nM for K562-RC and 44 nM for K562-RD, compared to 50 nM for K562. This drug induced apoptosis via the mitochondrial pathway. In K562 cells, alvespimycin induced cell cycle arrest in G0/G1. As a marker of HSP90 inhibition, a significant increase in HSP70 expression was observed. Our results suggest that alvespimycin might be a new therapeutic approach to CML treatment, even in cases of resistance to imatinib.